Echocardiographic diagnosis of left ventricular diastolic dysfunction: Impact of coronary artery disease. Issue 2 (14th December 2020) - Sharifov, Oleg F.; Murphy, John M.; Perry, Gilbert J.; Tallaj, Jose; Denney, Thomas S.; Prabhu, Sumanth D.; Gupta, Himanshu; Lloyd, Steven G.
Abstract: Background: In 2016, the American Society of Echocardiography (ASE) released guidelines for identifying left ventricular (LV) diastolic dysfunction (DD), but its ability to detect early hemodynamic abnormalities is not well established, especially in the setting of subclinical coronary artery disease (CAD). We hypothesize that the accuracy of ASE categorization of early LVDD is affected by knowledge of whether CAD history is present. Methods: We studied 34 patients (age 62 ± 7 years) with NYHA class I to II symptoms and with transthoracic echocardiography without findings suggesting myocardial disease (all with preserved LV ejection fraction), who underwent cardiac catheterization with high‐fidelity LV pressure measurement. Echocardiographic images were evaluated for LVDD using ASE algorithm without and with knowledge of CAD history and angiography findings. CAD was considered as having DD for the algorithm. Results: CAD was identified in 22 patients at catheterization (65%). Using ASE guidelines without including history of CAD or angiographic results, 29 patients were DD−, 3 were DD+ (all grade II), and 2 were indeterminate. Inclusion of CAD history recategorized 59% (n = 20) patients to DD+ (all grade I) from DD− ( P < .0001). Nineteen of the recategorized patients (95%) had increased isovolumetric relaxation time (IVRT). The addition of echocardiographic IVRT improved discrimination between DD− and DD+, when the presence of CAD is unknown. Conclusions: 2016‐ASE algorithm reasonably accurately identifies early LVDD at rest as reflected by LV catheterization when CAD is disclosed, but without knowledge of the presence of CAD, it underdiagnoses DD+ grade I. The addition of IVRT may improve early LVDD diagnostics.